Development inventory system: actual cost calculation method / Mohd Fhadhly Azhar - Azhar, Mohd Fhadhly (Faculty of Computer and Mathematical Sciences, 2007)
The inventory is an important feature in doing business. From a small business office to the large airport, inventory is used to manage their stock in order to keep running their business. The management of an inventory will give a large impact to a business. The emerging of web technology has changed the way people work. Web-based technology has solved the limitation that face by the stand-alone application which not allows people to work concurrently with the same data. This is why business field need this technology so that it can make communication and transaction faster. Because of this reason, this research has proposed a web-based application inventory system using .NET technology to replace the stand-alone application system. The new features added in this research are to calculate the actual cost of the item that kept in the inventory. The actual cost calculation allows the user to keep the actual cost of having the item in the inventory even though the item is keep changing it price by the supplier every month. The second feature is the stock age that allows the user to know the ages of the item kept in the inventory. In the conclusion, we can say that web-based application is an effective approach to be taken when dealing with massive information such as the cost of an inventory and the stock age that requires quick and immediate decision making. User can have better access to company inventory information as long as they have the Internet connection